1991
DOI: 10.1111/j.1469-8986.1991.tb01989.x
|View full text |Cite
|
Sign up to set email alerts
|

EEG Alpha Methodologies and Hypnotizability: A Critical Review

Abstract: This paper reviews empirical studies that assessed the relationship between EEG alpha indices and measures of hypnotic responding. Although there are confirmatory reports of such a relationship, these findings have not been corroborated in repeated attempts at replication. The research is characterized by poor design and statistical procedures that fail to control for various extraneous factors. Although a few positive findings have been tentatively identified, they await replication. Taken together, the avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…There is evidence for a higher proportion of occipital alpha waves in high suggestibles as compared to lows (e.g. London et al, 1968;Bakan and Svorad, 1969;Engstrom et al, 1970;Ulett et al, 1972;Morgan et al, 1974;Edmonston and Grotevant, 1975), but this fi nding was not replicated by some other studies (Barabasz, 1983;Perlini and Spanos, 1991).…”
Section: Hypnosismentioning
confidence: 78%
“…There is evidence for a higher proportion of occipital alpha waves in high suggestibles as compared to lows (e.g. London et al, 1968;Bakan and Svorad, 1969;Engstrom et al, 1970;Ulett et al, 1972;Morgan et al, 1974;Edmonston and Grotevant, 1975), but this fi nding was not replicated by some other studies (Barabasz, 1983;Perlini and Spanos, 1991).…”
Section: Hypnosismentioning
confidence: 78%
“…Early results were contradictory, however, with some studies reporting enhanced right occipital or occipital-parietal alpha (Crawford, Meszaros, & Szabo, 1989;MacLeod-Morgan, 1982;Ulett, Akpinar, & Itil, 1972), others reporting diminished bilateral occipital alpha (Saletu, 1987), and still others reporting no alpha changes in frontal, parietal, or occipital derivations during hypnosis (Meszaros & Banyai, 1978;Tebecis, Provins, Farnbach, & Pentony, 1975). This research was further confused by similarly contradictory relationships obtained between alpha EEGs and hypnotic susceptibility (Crawford & Gruzelier, 1992;Perlini & Spanos, 1991). Ina comprehensive critical review of the literature up to 1990, Perlini and Spanos (1991) found little support for an alpha-hypnotizability relationship, such serious methodological flaws in most of the hypnosis research as to render conclusions untenable, and no alpha differences between hypnotic and non-hypnotic conditions in the few well-designed and controlled studies.…”
Section: Electrophysiological Alterations During Hypnosis For Egoenhamentioning
confidence: 89%
“…As for the relationship between hypnotizability/hypnosis and relaxation, EEG studies have considered only short rest periods between suggestions as relaxation periods (De Pascalis, Ray, Tranquillo and D'Amico, 1998), or they did not investigate the possibly related changes in autonomic variables (Sabourin, Cutcomb, Crawford and Pribram, 1990;Perlini and Spanos, 1991;Graffin, Ray and Lundy, 1995;Williams and Gruzelier, 2001;. On the other hand, the modifications in autonomic and metabolic variables considered in Benson's definition are rather non-specific, because they can be observed in other conditions, i.e.…”
Section: What Is Relaxation? (Does Relaxation Exist?)mentioning
confidence: 97%